Strategies in translating Vietnamese teenager songs into English = Các chiến lược áp dụng trong dịch lời bài hát nhạc trẻ từ tiếng Việt sang tiếng Anh - Bùi, Thị Mai Hương (2021)
As music became a thriving industry around the world, the translation of song lyrics among languages acts as a stimulating tool for the development of the industry. Following this global trend, Vietnamese translators have also made remarkable efforts to create English translated versions of Vietnamese songs. However, the number of translated songs, especially teenager songs, remains limited while no standard has been established to assess these translations, therefore hindering the translated songs from appropriate recognition of audiences. In this paper entitled “STRATEGIES IN TRANSLATING VIETNAMESE TEENAGER SONGS INTO ENGLISH”, Vietnamese and English versions of song lyrics were compared and analysed based on Newmark’s theory of translation methods and procedures and Koller’s theory of formal equivalence in order to identify strategies frequently employed in the Vietnamese – English translation of teenager songs and their equivalent effect. Eight Vietnamese teenager songs were chosen on purpose as the subjects of the research. Strategies were acknowledged and then sorted out into adaptation and semantic translation methods. While analysing songs translated by applying semantic translation method, the researcher pointed out three subclasses of this method which are omission, addition and paraphrase.